Investigation of the isosteric heat of adsorption for supercritical methane on shale under high pressure - Shangwen Zhou; Hongyan Wang; Pengyu Zhang; Wei Guo (Adsorption Science & Technology)
The isosteric heat of adsorption (IHA) is one of the key thermodynamic variables for evaluating the interaction between shale and methane, which is rarely studied especially under high pressure. In this work, we conducted methane adsorption experiments at pressures up to 30 MPa and different temperatures on shale samples collected from Longmaxi formation in Sichuan Basin, China. Based on the definition of IHA and Langmuir adsorption model, we proposed a new method to analyze the IHA of methane on shale under four conditions. The calculated results show that the commonly used Clausius–Clapeyron equation overestimates the true isosteric heat of shale, especially under high pressure. IHA under four conditions yield a fixed order as q st,i-va  >  q st,r-va  >  q st,i+va  >  q st,r+va , indicating both the real gas behavior and the adsorbed-phase volume have a negative influence on it, and the effect of adsorbed-phase volume is dominant. Moreover, IHA at zero coverage ( q st 0 ) in Henry region determined by linear fitting can be regarded as a maximum value in the above four cases, which is independent of pressure and temperature. Therefore, q st 0 can be used as a unique descriptor to evaluate the adsorption affinity of the shale. This work modified the method to obtain the true IHA of supercritical methane on shale more accurately, which lays the foundation for future investigations of the thermodynamics and heat transfer characteristics of the interaction between high pressure methane and shale.